RFLP and cytogenetic evidence on the origin and evolution of allotetraploid domesticated peanut, Arachis hypogaea (Leguminosae) - Kochert, Gary; Stalker, H. Thomas; Gimenes, Marcos [UNESP]; Galgaro, Leticia [UNESP]; Lopes, Catalina Romero [UNESP]; Moore, Kim (Wiley, 1996)
Nuclear restriction fragment length polymorphism (RFLP) analysis was used to determine the wild diploid Arachis species that hybridized to form tetraploid domesticated peanut. Results using 20 previously mapped cDNA clones strongly indicated A. duranensis as the progenitor of the A genome of domesticated peanut and A. ipaensis as the B genome parent. A large amount of RFLP variability was found among the various accessions of A. duranensis, and accessions most similar to the A genome of cultivated peanut were identified. Chloroplast DNA RFLP analysis determined that A. duranensis was the female parent of the original hybridization event. Domesticated peanut is known to have one genome with a distinctly smaller pair of chromosomes ('A'), and one genome that lacks this pair. Cytogenetic analysis demonstrated that A. duranensis has a pair of 'A' chromosomes, and A. ipaensis does not. The cytogenetic evidence is thus consistent with the RFLP evidence concerning the identify of the progenitors. RFLP and cytogenetic evidence indicate a single origin for domesticated peanut in Northern Argentina or Southern Bolivia, followed by diversification under the influence of cultivation.
Keywords: Arachis; chloroplast DNA; domestication; groundnut; Leguminosae; peanut; RFLP; Arachis duranensis; Arachis hypogaea; Arachis ipaensis; Fabaceae